Edukasi Pemanfaatan Jahe Merah (Zingiber officinale var. rubrum) sebagai Terapi Pendukung Arthritis - Yuneka Saristiana; Fendy Prasetyawan; Lisa Savitri; M Wahyu Ariawan (Journal of Social Responsibility Projects by Higher Education Forum, 2025)
−This community service program was conducted in March 2025 in Gembleb Village, Pogalan District, Trenggalek Regency, East Java Province, an area with considerable natural resource potential in the form of red ginger (*Zingiber officinale* var. *rubrum*), which has not been optimally utilized. The problems faced by the community included limited knowledge regarding arthritis, dependence on chemical-based medications, and inadequate skills in processing herbal plants into beneficial products. In addition, the utilization of red ginger as a source of bioactive compounds, particularly gingerol, remained limited. This program aimed to improve community knowledge and skills in utilizing red ginger as a complementary therapy for arthritis through participatory education and training approaches. The implementation methods consisted of three stages: preparation, implementation, and evaluation. Educational sessions were conducted to enhance participants’ understanding of arthritis and inflammatory mechanisms, while training activities focused on the production of herbal products, including ginger beverages and instant ginger powder. Evaluation was carried out using pre-test and post-test assessments as well as direct observation of participants’ practical skills. The results showed significant improvements in both knowledge and skills. More than 80% of participants demonstrated increased understanding of arthritis and the benefits of red ginger and were able to independently process red ginger into herbal products. Furthermore, participants exhibited a more positive attitude toward the use of herbal therapy as a complementary treatment. This program contributed to enhancing community self-reliance and creating opportunities for the development of local potential-based herbal products.